PENGARUH PEMBERIAN KOMBINASI PUPUK MAJEMUK NPK (25:7:7) DAN NPK KEMASAN (10:55:10) TERHADAP PERTUMBUHAN VEGETATIF TANAMAN KAMBOJA JEPANG (ADENIUM OBESUM) - Susi Sulistiana (LPPM Universitas Terbuka, 2009)
The objectives of this research were (i) to identify the effects of combination of compound fertilizers of NPK (25:7:7) and package NPK (10:55:10) on vegetative growth Adenium obesum in stead of Japanese frangipani plant, and (ii) to obtain the best combination of dose of NPK (25:7:7) and package NPK (10:55:10) in order to improve plant vegetative growth of Adenium obesum. This experiment was conducted in employed completely random design with factorial pattern of 4 and three times repetition. Factor I, the dose of NPK (25:7:7) fertilizer in 4 levels of dose : 0.0 g/L; 0.5 g/L; 1.0 g/L; and 1.5 g/L. Meanwhile, Factor II, the dose of package NPK (10:55:10) was applied with 4 levels of dose : 0.0 g/L; 0.5 g/L; 1.0 g/L; and 1.5 g/L. The data obtained were analyzed using variance analysis (ANOVA) technique to identify the influence of the treatment towards variables measured and mean separation was evaluated using DMRT with 5% level of difference. The results show that the use of combination of compound fertilizers NPK (25:7:7) and package NPK (10:55:10) improves plant vegetative growth of Adenium obesum. However, the use of combination of NPK 0.0 g/L and package NPK 0.5 g/L shows unsatisafactory results. The combination of NPK 1.5 g/L and package NPK 1.5 g/L provides the best result in improving plant vegetative growth of Adenium obesum.